Determinants of interest in using e-wallets during the COVID-19 pandemic - Oktrivina, Amelia; Nelyumna, Nelyumna; Salwa , Adindafi Kartika (Sekolah Tinggi Ilmu Ekonomi Indonesia Jakarta, 2023)
Due to the virus COVID-19 outbreak, the government has implemented various policies to limit public activities outside the home, which has led many individuals to shift to online services. Financial Technology (FinTech) has emerged as a viable solution that utilizes digital technology, allowing people to fulfill their financial needs without face-to-face interactions with sellers. This study analyzes how perceptions of benefits, ease of use, and risks influence interest in using FinTech, specifically e-wallets. The study focuses on residents of Jabodetabek and employs a quantitative research method. Primary data was collected through questionnaires completed by 100 respondents. The findings indicate that perceptions of benefits and ease of use positively and significantly impact interest in using FinTech (e-wallets). Conversely, perceptions of risk have a negative but statistically insignificant effect on interest in using FinTech (e-wallets).